Effect of Humus-Like Organic Substances and Beneficial Bacteria on Soil Agrochemical Parameters in Reducing the Amount of Heavy Metals in the Soil - Boynazarov Bakhron Raimovich; Djumaniyazova Gulnara Ismailovna (American Journal of Biology and Natural Sciences, 2024)
The article presents data on the positive effect of the new generation bacterial fertilizer of complex action Teria-S, organic fertilizer K-Gumat, biopreparation Serhosil and mineral fertilizer (NP) on the agrochemical parameters of soils contaminated with heavy metals at the Almalyk Mining and Metallurgical Plant when growing wheat plants.